PERMAINAN TRADISIONAL DIGUNAKAN UNTUK MEMBINA KARAKTER ANAK - Binti Syarofah, Siti Anisarahayu, Linda Wahyu Setyaningrum (Pelita - Jurnal Penelitian Mahasiswa UNY, 2010)
Initially, students gain character education through lectures and brief advice from teachers.However, the way has been found not to give direct experience of students but only provides acasuistic theory. This research aims to improve understanding of the values of character educationthrough traditional games for students in kindergarten ABA Karangmalang grade B.2. Traditionalgames that are used in this research is cublak‐cublak suweng, dakon, jamuran, and ular naga.This research is classroom action research model of Kemmis and McTaggart. The seriesconsisted of planning, action, observation, and reflection. Subject of this reseacrh is the students ofkindergarten ABA Karangmalang grade B.2, and the object of this research is value of charactereducation which integrated in tradisional games. Data obtained through observation by four cycles,and an interview to the guardian class. Data analysis using of qualitative descriptive techniques.At the time of the learning process, students are seen active, happy and able to follow aseries of activities well. The result is the students understand about the value of character educationwhich provided through each of the traditional game and its application in daily activity.Key word: traditional games, character, students